What microeconomic fundamentals drove global oil prices during 1986-2020? - Anastasios G. Malliaris; Mary E. Malliaris (Journal of Risk and Financial Management, 2021)
The global financial crisis of 2007-2009 caused major economic disturbances in the oil market. In this paper, we consider five variables that describe the microeconomics of the supply of and demand for oil, and evaluate their importance before, during and after the global financial crisis. We consider five dissimilar regimes during the period of January 1986 to the end of 2020: two regimes prior to the global financial crisis, the regime during the crisis, and two regimes after the crisis. The main hypothesis tested is that oil fundamentals of supply and demand remained important, even though the five regimes were dissimilar. We built five boosted and over-fitted neural networks to capture the exact relationships between spot oil prices and oil data related to these prices. This analysis shows that, while the inputs into an accurate neural network can remain the same, the impact of each variable can change considerably during different regimes.
Keywords: 330; 2007-2009 global financial crisis; neural network methodology; oil price regimes; structural breaks